PENGARUH PAPARAN KEBISINGAN TERHADAP JUMLAH SPERMATOZOA MENCIT JANTAN (Mus musculus L.) YANG DIBERIKAN EKSTRAK BIJI ANGGUR (Vitis vinifera L.) - Ghestiara Pusphita Hannum Siregar (2020)
Continuous exposure to noises that exceeds the threshold limit could change the male hormone system, which leads to formation of oxidative stress, and disrupt the semen quality. This condition can be reduced by the use of antioxidant. Grape seed is one of the antioxidants that contain phenol components that have Resveratrol compounds. This research aimed to discover the effect of noise exposure on the amount of spermatozoa of male mice given grape seed extract. This study used a post-test only control group, the research subjects were 30 male Swiss Webster mice divided into 5 groups: group A (treatment control) was not given noise exposure and was not given grape seed extract, group B (negative control) was not given noise exposure and was given grape seed extract, groups C, D, E (treatment group) were given noise exposure with sequential intensities of 65 dB, 85 dB, 105 dB. The treatment was given for 33 days. The results of this research indicated that noise exposure with different intensities of 65 dB, 85 dB, 105 dB reduce the spermatozoa count of male Swiss Webster mice given with grape seed extract. One Way Anova test was used for the result of this study, with p-value of 0.001. Conclusion: There are differences between the control group and treatment group. Provision of noise exposure with a value above the threshold limit reduce the amount of male Swiss Webster mice spermatozoa given with grape seed extract